Decision-making process in investment projects - Moutinho, Nuno (2014)
We present projects evaluation approaches in what decision should be based. We try to understand what we have to take into account in a project analysis, knowing that we have to consider much unmeasured aspects, like non non-financial areas. We verify how all aspects are used and analysed in the project appraisal. We also desire to understand if companies have adequate tools and methods to correctly analyse and to take decisions in a project evaluation. In this study we identify several aspects that are able to influence investment projects evaluation and decision-making process. An investment is not a mere financial activity, but involves a diversity of behavioural factors, organizational and business perception, which should be properly adjusted to invest with success. Investment decision-making should take into account non financial aspects, mainly, through some evaluation’s format and method. As non financial aspects have an intangible nature, they are difficult to estimate, and cause a subjective analysis to project evaluators, it is important to develop an objective and tangible method that incorporates and quantify all non financial aspects together in project evaluation.